ANALISIS WILAYAH JELAJAH MONYET EKOR PANJANG (Macaca fascicularis) DI TAMAN WISATA ALAM MENIPO, DESA ENORAEN, KECAMATAN AMARASI TIMUR, KABUPATEN KUPANG, PROVINSI NUSA TENGGARA TIMUR - Tukan, Jimilus; Purnama, Maria M. E.; Riwu Kaho, No P.L.B. (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2022)
monkeys (Macaca fascicularis). This research was conducted at Menipo Natural Tourism Park (NTP), Enoraen Village, East Amarasi Subdistrict, Kupang Regency, East Nusa Tenggara which was conducted for 1 month, from September to October 2021. The study used Zoatrack's WebGIS method, which determined Macaca’s home range using Minimum Concex Polygon (MCP) method and core area using Kernel Utilization Distribution. Moreover, the analysis of data were conducted with statistics descriptive analysis. The results showed that the home range that has been analyzed using Minimum Convex Polygon (MCP) is 142.45 ha and this area of long-tailed monkeys (Macaca fascicularis) home range lies in almost all of the Menipo NTP area with its forest characteristics that consists of dry forests, brackish forests, and coastal forests. The results of the core area analysis using Kernel Utilization Distribution showed that the area of the core area was 53.63 Ha. The results of the core area also shows that there is one particular of core area that is often visited by long-tailed monkeys (Macaca fascicularis). This is due to the abundance of food and trees as their resting place in the Menipo NTP area.